Irrigated wheat subjected to inoculation with Azospirillum brasilense and nitrogen doses as top-dressing - Alves, Cleiton J. [UNESP]; Arf, Orivaldo [UNESP]; Ramos, Ane F. [UNESP]; Galindo, Fernando S. [UNESP]; Nogueira, Lais M. [UNESP]; Rodrigues, Ricardo A. F. [UNESP] (Univ Federal Campina Grande, 2017)
The use of Azospirillum brasilense in the wheat crop still presents contradictory results; thus, it is necessary to identify ideal conditions to obtain satisfactory results. The objective of this study was to investigate the interaction between Azospirillum brasilense and nitrogen doses in a wheat cultivar, conducted with irrigation in the Cerrado region of Mato Grosso do Sul. The experimental design was randomized blocks with a 4 x 2 factorial scheme, four nitrogen doses ( 0, 40, 80 and 120 kg ha(-1)) applied as top-dressing, associated or not with inoculation of wheat seeds with Azospirillum brasilense. The results show that there was no interaction between N and inoculation. The isolated effect of Azospirillum brasilense promotes an increase in plant height and number of grains per spike. Nitrogen doses promotes significant increases in leaf N content, plant height, number of grains per spike, number of spikes per square meter and grain yield. The conditions under which the experiment was conducted favored the development of the crop, not interfering with grain yield due the inoculation with Azospirillum brasilense.
Keywords: Triticum aestivum L.; nitrogen fertilization; plant growth-promoting bacteria; Cerrado